Apropriação do conto maravilhoso pela telenovela brasileira: configuração e estratégias - Lima, Denise Aristimunha de (2018)
The research proposal of this study is to analyze Brazilian television production and its appropriations, delimiting the scope of our study field to the national network TV Globo and the telenovela (Brazilian soap opera) Meu Pedacinho de Chão. Our research problem is centered on the following questions: How does Brazilian telenovelas appropriate elements from the magic tales? What configuration stems from this appropriation? What are the strategies involved? In this sense, the main objective of the present study is to analyze how television appropriates the magic tales for the production of telenovelas, including its configuration and strategies. Our specific objectives are: to investigate the concept of narrative in the literary perspective and in the dimension proposed by the Propp’s structure of the magic tale; to examine the origin of the narrativity concept, applying the Greimasian semiotic approach, and its relation with fictional television production; to investigate the levels of articulation present in the semiotic theory and its application to television production; to examine the characteristics of the genre fiction, updated in the subgenre telenovelas; to relate the characteristics of telenovelas to the magic tale; to analyze, from the perspective of the Greimas’ semiotic inspiration model, the telenovela object of this study in order to identify the assumed configuration and the paratextual, intertextual, and intratextual strategies adopted. The theoretical-methodological course was based on the principles of French semiotics, developed by Greimas and complemented by his followers, and on the methodological proposal developed by the research group Comunicação Televisual (ComTV). It concerns the three levels of analysis, recognized in Meu Pedacinho de Chão: paratextuality – referring to the environment surrounding the empirical object; intertextuality – referring to the relation of the telenovela with its model and with other texts; and intratextuality – regarding content- and expression-level relations. Our results show a comparison of the semantic and syntactic devices present in the three analyzed weeks. We were also able to recognize the articulation between levels, with emphasis on the expression, identified in the handmade scenographic architecture, in the diversity of colors, in the eccentricity of costumes and makeup, in the characters' gestures and facial expressions, and in the use of graphic animation forms. With our analysis, we could reiterate the concept of narrativity proposed by Greimas as the organizing principle of Meu Pedacinho de Chão, which mixes the fantasy of the unreal world (which has its own laws) with the harsh reality of the factual world.